Perceptions of Students with Disabilities on Reasonable Learning Accommodations at Universitas Negeri Padang - Almayeni, Meza; Marlina, Marlina (The Center for Disability Studies and Services Brawijaya University, 2023)
Based on the initial survey conducted, there are still obstacles faced by students with disabilities to get proper accommodation in learning at Padang State University (UNP). These accommodations are in the form of model, media, material, and learning evaluation accommodations. This study was conducted with the aim of knowing the perceptions of students with disabilities regarding the feasibility of learning accommodations available at UNP. The research method used descriptive quantitative with 49 research subjects from 2015-2022 who came from different study programs and types of disabilities. The data collection technique uses online surveys and questionnaires through the Google Form platform which is distributed on social media. The results showed that learning model accommodation was not feasible, learning media accommodation was not feasible, learning material accommodation was moderately feasible, and learning evaluation accommodation was moderately feasible in the perception of UNP students with disabilities.